Internal Control Systems and Performance of Government Institutions in Kabale District: A Case of Kabale Regional Referral Hospital - Grace, Kihembo (Kabale University, 2022)
A Dissertation Submitted in Partial Fulfilment of the Requirement for the Award of Master of Business Administration of Kabale University